Wolfgang Streeck's conception of the crisis-phase of democratic politics: a post-Keynesian critique. Issue 2 (2nd April 2016) - Dow, Geoff
ABSTRACT: Depictions of the politics of crisis in advanced societies (what crisis is and what can be done) continue to pit different strands of political science and heterodox political economy against each other. Economic sociologist Wolfgang Streeck's contributions to these controversies have emphasised 'embeddedness', or the need for economies to incorporate non-functional or deliberated elements which allow functional and market-focused processes to play themselves out. Streeck's recent writings on debt-induced crisis nonetheless accept too much orthodox liberal disquiet: most fatefully, a contempt for politics based on what seems to be an untenable assertion – that rich societies have hit the limits of their capacity to increase taxation. Capitalism has entered an 'end point', he claims. This article presents, again, contrary evidence and offers suggestions for a revised heterodox understanding of capitalism's current malaise.